Analysis of Stakeholders’ Interest and Influence in Non-Timber Forest Products Marketing: A Case Study in the Forest Management Unit Batutegi, Lampung - Dwi Kurniati; Hardjanto; Soni Trison (Jurnal Sylva Lestari, 2023)
Stakeholders are involved in the management of the Forest Management Unit (FMU) Batutegi, including the marketing of non-timber forest products (NTFP). The performance of NTFP marketing in the FMU Batutegi currently has not provided optimal benefits, especially for forest farmers. Stakeholders have divergent interests and influence in NTFP marketing. The research aimed to analyze the interests and influence of each stakeholder and the relationship between stakeholders in the marketing of NTFP. Data collection was carried out through observation and interviews. Interviews were conducted with informants and stakeholders. The scoring method was used in this study. Data and information were analyzed qualitatively. The study results showed that the marketing of NTFP in the FMU Batutegi involves 15 stakeholders. There are 11 parties with moderately high interest and 8 parties with moderately high influence. FMU Batutegi is the most responsible party or central actor in NTFP marketing because it has relationships with important stakeholders, has the most relationships, and can control the flow of information in the network. The method’s usefulness for understanding stakeholders’ position in NTFP marketing. The study result is expected to be utilized by policymakers to facilitate cooperation between stakeholders to achieve optimal NTFP marketing performance. Keywords: FMU Batutegi, marketing, non-timber forest products, stakeholders